114 Non-coding RNAs in bovine mammary glands. (7th December 2018) - Zhao, X; Do, D; Ibeagha-Awemu, E
Abstract: Non-coding RNAs (ncRNAs) are a class of untranslated RNA molecules that have emerged as new regulators of gene expression. The roles of ncRNAs including small interfering RNA, microRNA (miRNA), PIWI-interacting RNA, small nucleolar RNA, long non-coding RNA (lncRNA) and circular RNA, in the regulation of traits of economic importance in livestock are gaining more importance. MiRNA, the most studied class of ncRNA in bovine, is known to control the activities of about 60% of all protein-coding genes and regulate almost every cellular process investigated in mammals. The recent release of miRbase v22 (2018) and NONECODE database (2017) listed about 1, 100 miRNAs and 22, 386 lncRNAs transcripts identified in the bovine genome. Aided by advances in deep sequencing technologies and bioinformatics tools, the roles of ncRNAs, in particular miRNAs and lncRNAs, in mammary gland (MG) functions and disease are beginning to emerge. This talk will focus on the roles of miRNA and lncRNA in MG health and productivity. The evidence of miRNA roles in lactation signalling, nutritional and disease regulation will be highlighted based on our own findings and relevant literature. For instance, miR-29b/miR-363 and miR-874/miR-6254 are important mediators of the transition signals between lactogenesis and galactopoiesis, and galactopoiesis and involution, respectively, while miR-199c, miR-199a-3p, miR-98, miR-378, miR-148b, miR-21-5p and miR-200a are crucial for the MG response to diets rich in unsaturated fatty acids. Different approaches ( in vivo versus in vitro ) for exploring miRNA roles in response to mastitis, an important disease of the MG will be highlighted. Furthermore, possible roles of lncRNA in MG functions, such as responses to diets and the implication of the colocation of lncRNA genes with QTL for milk traits and mastitis, will be discussed. Finally, potential application of emerging genome editing technologies for ncRNA functional studies and implication for MG health and productivity will be presented.